Pemetaan Konseptual Strategi Retensi Karyawan Generasi Z dalam Perspektif Teori Motivasi - Hasni; Nur zazlin; Muhammad Adriansyah; Aprin aga Yohanis; Chris Dayanti Br. Ginting (Journal of Accounting, Economics, and Business Education, 2025)
Generation Z has become an increasingly significant segment of the workforce, bringing unique characteristics and expectations that differ from previous generations. As a result, organizations must understand the motivational patterns that influence their retention. This study aims to map retention strategies for Generation Z employees through a literature-based approach using several motivation theories, including Maslow’s Hierarchy of Needs, Herzberg’s Two-Factor Theory, Self-Determination Theory, and Expectancy Theory. The findings indicate that Generation Z seeks not only financial compensation but also flexibility, continuous development opportunities, a supportive work environment, and fair and meaningful rewards. The integration of these theories demonstrates that Generation Z’s retention is shaped by the fulfillment of basic needs, intrinsic motivation, psychological needs, and perceptions of fairness and relevance of rewards. This study concludes that effective retention strategies for Generation Z must be holistic and designed to meet their comprehensive needs, enabling organizations to retain young talent more sustainably.